Analisis Pengaruh Consumer Innovativeness Dan Market Maven Terhadap Opinion Leadership - Fakhrudin, Arif (Jurnal Manajemen Bisnis, 2017)
Consumer in this time very inovatif conducting a process of product purchasing which they wish, at this situation consumer cope to look for the information as much as possible hitting product which they wish the. The information is obtainable from assorted of source and assorted of media. Usually consumer very paying attention to of problem categorize the product, do not take as problem of to hit the price problem, searching good quality, good model and also recognized brand.This research measure the influence of Consumer Innovativeness and Market Maven to Opinion Leadership on the use of transport service providers. Independent variable in research is Consumer Innovativeness and Market Maven. While variable dependen in this research is Opinion Leadership. Result from test of ANOVA or F Test got by F calculate 269.995 with level signifikan 0.000. so that probabilitas 0.000 compared to smaller level signifikan of equal to 0.05, hence can be said that by variable of Consumer Innovativeness and Market Maven by simultan have an effect on to Opinion Leadership, inferential that independent variable have an effect on the signifikan to variable dependen.